More tropical cyclones in a cooler climate?. Issue 16 (22nd August 2015) - Sugi, Masato; Yoshida, Kohei; Murakami, Hiroyuki
Abstract: Recent review papers reported that many high‐resolution global climate models consistently projected a reduction of global tropical cyclone (TC) frequency in a future warmer climate, although the mechanism of the reduction is not yet fully understood. Here we present a result of 4K‐cooler climate experiment. The global TC frequency significantly increases in the 4K‐cooler climate compared to the present climate. This is consistent with a significant decrease in TC frequency in the 4K‐warmer climate. For the mechanism of TC frequency reduction in a warmer climate, upward mass flux hypothesis and saturation deficit hypothesis have been proposed. The result of the 4K‐cooler climate experiment is consistent with these two hypotheses. One very interesting point is that the experiment has clearly shown that TC genesis is possible at sea surface temperature (SST) well below 26°C which has been considered as the lowest SST limit for TC genesis. Key Points: The 4K‐cooler climate experiment is conducted using a high‐resolution AGCM Number of TCs is significantly increased in the 4K‐cooler climate Tropical cyclone genesis can occur at SST well below 26°C